Strategi Guru dalam Meningkatkan Mahāratul Kitābah: Integrasi Pendekatan Interaktif dan Metode Imla’ Manqūl pada Siswa Sekolah Menenegah Pertama - Lalu Wahyu Putra Utama; Reza Al-Ayyubi (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2025)
This study analyze teacher strategies in improving writing skills (mahārah kitābah) students through an integrative approach. Kitābah learning faces its own challenges, low mastery of vocabularies ‘mufradāt’, inappropriate learning methods make mahārah kitābah a lesson that is still difficult to understand and master for students. This study aims to analyze the strategies of Arabic language teachers in improving the writing skills of grade VII students at Ibnu Abbas Lombok Timur Junior high school. Difficulties faced by students include errors in identifying letters, connecting letters and errors in writing that have similar letter sounds. The study uses a qualitative-descriptive approach, namely understanding the phenomenon of teacher strategies with the integration of interactive learning approaches and imla’ manqūl methods in improving student skills. To obtain comprehensive data, this study uses observation, interviews and documentation. The results of this study indicate that in complex imla’ learning, requiring skills and experience, teacher strategies play an important role in determining the success of learning, especially mahārah kitābah. The integration of interactive approaches through tikrār, question and answer, and imla’ manqūl can improve writing skills in seventh grade students at Ibnu Abbas Junior High School, East Lombok. This improvement in skills can be seen from students' ability to identify words and sentences and be able to write correctly according to the material that has been studied. This research can be conceptually a reference for integrative learning strategies to facilitate students in mastering writing skills. In addition, practically, the research is used as a practical guideline for Arabic language teachers in implementing interactive learning in kitābah learning, especially for elementary level students.